Cation Additive Enabled Rechargeable LiOH‐Based Lithium–Oxygen Batteries. (19th November 2020) - Bi, Xuanxuan; Li, Matthew; Liu, Cong; Yuan, Yifei; Wang, Hao; Key, Baris; Wang, Rongyue; Shahbazian‐Yassar, Reza; Curtiss, Larry A.; Lu, Jun; Amine, Khalil
Abstract: Lithium–oxygen (Li–O2 ) batteries have attracted extensive research interest due to their high energy density. Other than Li2 O2 (a typical discharge product in Li–O2 batteries), LiOH has proved to be electrochemically active as an alternative product. Here we report a simple strategy to achieve a reversible LiOH‐based Li–O2 battery by using a cation additive, sodium ions, to the lithium electrolyte. Without redox mediators in the cell, LiOH is detected as the sole discharge product and it charges at a low charge potential of 3.4 V. A solution‐based reaction route is proposed, showing that the competing solvation environment of the catalyst and Li + leads to LiOH precipitation at the cathode. It is critical to tune the cell chemistry of Li–O2 batteries by designing a simple system to promote LiOH formation/decomposition. Abstract : Achieving rechargeable LiOH‐based lithium–oxygen batteries is challenging without a redox mediator or catalysts. By adding a cation additive, LiOH is confirmed as the discharge product in the lithium–oxygen battery and it reversibly charges at a low voltage.